REVIEW ON NATIONAL IDENTITY IN ARCHITECTURE THROUGH THE UNDERSTANDING OF ITS ROLES, TYPOLOGIES AND THEMES - Muhamad Hanafi Rahmat; Alice Sabrina Ismail (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
National identity is defined as a sense of belonging or ownership to a country or a nation related to the idea of unity for a country, represented by recognizing similarities in tradition, culture, language, and political ideology. Understanding national identity in architecture will direct us to study its roles, typologies, and themes. Architecture describes its own identity based on the conditions of the location it was developed which translates into physical form. It is not easy to understand what identity is and how national identity can be described in different national socio-political conditions. This study compiles the scholars’ ideologies and viewpoints through literature review and direct observations on the roles, typologies, and themes of national identity in architecture. Interpretative paradigm was used to interpret and understand the factors that shaped the ideology of national identity in architecture. This paper discusses the roles of architectural national identity from the community perspective (project identity) and government’s perspective (‘sub-national identity’, ‘supra-national identity’ and ‘private identity), the typologies - natural identity, artificial identity (manufactured identity), forced identity and the themes - typology, remembrance (memorial) and geopolitics. This study used a qualitative approach in which data were collected from ideological case studies and scholarly views through literature review. As a result, the roles determine why architecture was initiated, typologies allow us to understand the categorization and classifications of architecture and themes lead us to appreciate the hidden meaning of architecture. This study will be used as a reference and guide by architects, designers, planners, policymakers, and authorities to understand more about national identity in architecture.